Dynamic Studies on Kinetic H2/D2 Quantum Sieving in a Narrow Pore Metal–Organic Framework Grown on a Sensor Chip. Issue 46 (24th June 2019) - Paschke, Benjamin; Denysenko, Dmytro; Bredenkötter, Björn; Sastre, German; Wixforth, Achim; Volkmer, Dirk
Abstract: The separation of deuterium from hydrogen still remains a challenging and industrially relevant task. Compared to traditional cryogenic methods for separation, based on different boiling points of H2 and D2, the use of ultramicroporous materials offers a more efficient alternative method. Due to their rigid structures, permanently high porosity, tunable pore sizes and adjustable internal surface properties, metal–organic frameworks (MOFs), a class of porous materials built through the coordination between organic linkers and metal ions/clusters, are more suitable for this approach than zeolites or carbon‐based materials. Herein, dynamic gas flow studies on H2 /D2 quantum sieving in MFU‐4, a metal‐organic framework with ultra‐narrow pores of 2.5 Å, are presented. A specially designed sensor with a very fast response based on surface acoustic waves is used. On‐chip measurements of diffusion rates in the temperature range 27–207 K reveal a quantum sieving effect, with D2 diffusing faster than H2 below 64 K and the opposite selectivity above this temperature. The experimental results obtained are confirmed by molecular dynamic simulation regarding quantum sieving of H2 and D2 on MOFs for which a flexible framework approach was used for the first time. Abstract : Materials science : Metal–organic framework MFU‐4, with ultra‐narrow pores of 2.5 Å, has been found suitable for kinetic quantum sieving of H2 and D2 using a specially designed surface acoustic wave sensor with a very fast response. On‐chip measurements of diffusion rates in the temperature range 27–207 K reveal a quantum sieving effect, with H2 diffusing faster than D2 above 64 K (see figure)